Population dynamics and growth of Galinsoga ciliata in relation to method of cultivation, crop type and altitude - MISRA, J; PANDEY, H N; TRIPATHI, R S (The Indian Journal of Agricultural Sciences, 2013)
Population dynamics and growth (dry-matter yield) of Galinsoga ciliata (Rafin.) Blake a serious weed in hill agroecosystem of Meghalaya was studied for two years in radish (Raphanus sativus L.) and maize (Zea mays L.) fields under slash and burn agriculture (jhum) and terrace cultivation situated at high and low altitudes of Meghalaya, north-east India. Two to three seedling cohorts were recruited in the crop fields at the low altitude, while at high altitude seedlings were recruited ’invariably in three successive cohorts. Seedling emergence in the first cohort was significantly higher than in the second and/or third cohort. Associated crop, method of cultivation and altitudinal variation significantly influenced seedling recruitment and survivorship and half lives of cohorts of G. ciliata.